Privacy, Information Technology, and the Educational Process - Tweed W. Ross (Educational Considerations, 1999)
In the middle of the Information Age (Toffler) educational institutions have focused on a wide range of issues relative to the application of new information technologies. Child safety on the worldwide has been a great concern for schools.